Implementasi Layanan Cloud Computing Software As a Service Pada Usaha Mikro Kecil dan Menengah - Rahardian, Rifky Lana; Linawati, Linawati; Sudarma, Made (Majalah Ilmiah Teknologi Elektro, 2018)
MSMEs (Micro and Small and Medium Enterprises) have an important role now in the ASEAN economy. 96% of companies in ASEAN are MSMEs. Although MSMEs have shown their role, they still face various obstacles and constraints such as lack of information, weak branding, promotion and infrastructure. The application of information technology will certainly make it easier for MSMEs to strengthen branding, business processing and enable cooperation with other parties to provide added value to MSMEs. The application of cloud computing or cloud computing is considered suitable for MSMEs that have limited resources in the form of capital, human resources (HR) and information technology infrastructure. Responding to the importance of the application of information technology to these MSMEs, the research aims to design and build systems that can facilitate MSMEs by utilizing cloud computing technology with SAAS (software as a service). The system has been tested by testing carried out using the blackbox method which is considered to be running optimally, functionally the system built can produce the output expected by the MSMEe participants. Usability testing to measure the level of satisfaction (user satisfaction) with the usability scale (SUS) system method is also felt necessary so that the system is designed and built according to user needs and satisfaction. With the results of the calculation of SUS 72.25 which means that it belongs to class B or above the average makes SAAS cloud computing services a system that can be accepted by MSMEs participants in supporting their business.